Processes of students’ effort exertion, competence beliefs and motivation: Cyclic and dynamic effects of learning experiences within school days and school subjects - Malmberg, Lars-Erik; Martin, Andrew J. (Contemporary educational psychology, 2019)
•We investigated cyclic and dynamic intraindividual processes.•We investigated novel lagged variables: within-day and within-school-subject.•Competence beliefs and autonomous motivation were sustained within school subjects.•Controlled motivation was sustained both within days and school-subjects.•We found both self-enhancing and self-diminishing lagged effects. We pose a process perspective of learning experiences of effort exertion, competence beliefs, and motivation (autonomous and controlled motivation). Following a process-model of cyclic (“self-sustaining”, auto-regressive) and dynamic (“self-enhancing” and “self-diminishing”, cross-lagged) associations over time, we investigated the effects of lagged within-day and within-school-subject constructs, and associations with teacher-perceptions of each student (nteacher=22). In total, 231 students in grade 5 and 6 in primary schools in England (108 boys and 123 girls; Mage = 10.5 years) responded to the Learning Experience Questionnaire an average of 15.1 time-points during a week (SD = 3.3; Range = 10–26, in total 3490 time-points). Multilevel structural equation models (MSEM) showed that effort exertion was the least self-sustaining. Competence beliefs and autonomous motivation were sustained within school-subjects. Controlled motivation was sustained both within days and school subjects. Teachers were more involved with students who felt less competent during the week. Within days controlled motivation showed a self-enhancing effect on effort, while effort showed a self-diminishing effect on controlled motivation. Within school-subjects controlled motivation showed a self-diminishing effect on competence belief and autonomous motivation. Overall our study provides insights into cyclic and dynamic processes of learning experiences in real-time and how these processes are related with student-teacher interactions.